2016
DOI: 10.1056/nejmoa1515725
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine for the Prevention of Chemotherapy-Induced Nausea and Vomiting

Abstract: BACKGROUND We examined the efficacy of olanzapine for the prevention of nausea and vomiting in patients receiving highly emetogenic chemotherapy. METHODS In a randomized, double-blind, phase 3 trial, we compared olanzapine with placebo, in combination with dexamethasone, aprepitant or fosaprepitant, and a 5-hydroxytryptamine type 3–receptor antagonist, in patients with no previous chemotherapy who were receiving cisplatin (≥70 mg per square meter of body-surface area) or cyclophosphamide–doxorubicin. The dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
210
4
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 338 publications
(252 citation statements)
references
References 25 publications
14
210
4
8
Order By: Relevance
“…The benefit of adding olanzapine to a triplet aprepitant/fosaprepitant–5-HT 3 RA–dexamethasone regimen for the control of nausea has been evaluated in a phase III study in 380 patients receiving cisplatin- or AC-based HEC [77]. Nausea prophylaxis was the primary endpoint.…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of adding olanzapine to a triplet aprepitant/fosaprepitant–5-HT 3 RA–dexamethasone regimen for the control of nausea has been evaluated in a phase III study in 380 patients receiving cisplatin- or AC-based HEC [77]. Nausea prophylaxis was the primary endpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, olanzapine, a 5-HT 2 , 5-HT 3 , D2, M 1 , M 3 , H 1 , and alpha-2 receptor antagonist, has also been used for patients with nausea and vomiting; however, efficacy studies have only been performed in chemotherapy and palliative care trials. 1820 …”
Section: Update and Discussion Of Recent Studiesmentioning
confidence: 99%
“…Olanzapine is another antipsychotic drug whose effect is manifested through blockade of multiple neurotransmitter receptors. Navari et al (2016) reported on a randomized, double-blind, phase-3 trial comparing olanzapine with placebo, in combination with dexamethasone, aprepitant or fosaprepitant, and 5-HT3 receptor antagonist in patients receiving cisplatin or AC. Olanzapine significantly improved nausea prevention, as well as the prevalence of a CR, among patients receiving HEC.…”
Section: Discussionmentioning
confidence: 99%